Development and performance of palm oil industry in Malaysia and Indonesia - Md Ali, Anizah; Mohd Jani, Mohd Fauzi (Universitas Islam Riau Indonesia, 2010)
Palm oil is a major vegetable oils traded in market place, whereas Malaysia and Indonesia are the main producer and exporter of world palm oil. Palm oil is a strategic crop for Malaysia and Indonesia economy due to export earning and employment opportunity. Historically, palm oil is originated from West Africa and commonly known today as a vegetable oil. It is currently available in more than 100 countries and is used in such food applications as margarine, shortening, potato chips, cake mixes and non-food applications like soap as well as biodiesel as new demand of palm oil. The versatile and benefit of palm oil boosted the consumption of palm oil in the market place. The objective of this paper is to analyze the development of palm oil industry in Malaysia and Indonesia in terms of production, area cultivation and yield as well as export. This paper also discussed collaboration between Malaysia and Indonesia to tackle palm oil issues in global market.